Mask-free generation of multicellular 3D heterospheroids array for high-throughput combinatorial anti-cancer drug screening. (5th December 2019) - Yang, Wenguang; Cai, Shuxiang; Yuan, Zheng; Lai, Youbin; Yu, Haibo; Wang, Yuechao; Liu, Lianqing
Abstract: Since cancer incidence and mortality are rapidly growing worldwide, it is imperative to develop the effective tumor models in vitro for anti-cancer drug screening. Cellular spheroid as an excellent simple 3D model can bridge the gap between cell culture and live tissue. Although numerous approaches for generating cellular spheroids emerges, the long cultivation time and the heterospheroids formation with multiple cell types are still challenging. In the present study, a mask-free method of multicellular heterospheroids arrays formation using digital micromirror device (DMD)-based hydrogel fabricating system and microfluidic system is proposed. Microwell arrays were designed and manufactured online based on shadowed light which shows high flexible. Besides, heterospheroids with multiple cells controlled in different ratios can be generated and cultured for a long time in microfluidic system. Furthermore, the drug screening shows that heterospheroids have high rate of drug resistance compared with homospheroids and combinatorial drugs works better than the single drugs. These studies provide a 3D heterospheroids generating process for high-throughput combinatorial anti-cancer drug screening with potential cancer therapeutic application. Graphical abstract: Herein, a mask-free method of multicellular heterospheroids arrays in combination with the microfluidic system for high-throughput combinatorial anti-cancer drug screening is investigated. Drug screening shows that combinatorial drugs works better than the single drugs and heterospheroids formed by cancer cells and fibroblasts cells show high drug-resistance compared with homospheroids.Unlabelled Image Highlights: A mask-free method of multicellular heterospheroids arrays formation using digital micromirror device (DMD)-based hydrogel fabricating system and microfluidic system is proposed. Microwell arrays are designed and manufactured online based on shadowed light which shows high flexible. Heterospheroids with multiple cells controlled in different ratios can be generated and high-throughput combinatorial anti-cancer drug screening is performed.